DETERMINANTS OF IMPULSIVE BUYING BEHAVIOR ON TIKTOK SHOP GENERATION Z - Made Setini; Ni Kadek Cerina Puspa Dewi; I Gusti Ayu Agung Istri Sari Dewi (Jurnal Manajemen dan Bisnis Performa, 2026)
The rapid growth of social commerce has significantly influenced consumer purchasing behavior, particularly among Generation Z. TikTok Shop has emerged as a popular platform that integrates entertainment and shopping, increasing the potential for impulsive buying behavior. This study aims to examine the effect of free shipping, advertising, and price perception on impulsive buying through TikTok Shop among Generation Z in Denpasar, both partially and simultaneously. This research employs a quantitative associative approach. The population consists of Generation Z university students in Denpasar who have made purchases through TikTok Shop. A total of 100 respondents were selected using purposive sampling, and data were collected through a structured questionnaire using a five-point Likert scale. The data were analyzed using multiple linear regression analysis with SPSS. The results indicate that free shipping, advertising, and price perception each have a positive and significant effect on impulsive buying. Simultaneously, these three variables also significantly influence impulsive buying behavior among Generation Z TikTok Shop users in Denpasar. Among the variables tested, advertising is the most dominant factor in encouraging impulsive buying. These findings suggest that attractive promotional strategies, engaging advertising content, and positive price perceptions play a crucial role in stimulating impulsive buying behavior on social commerce platforms.This study provides theoretical contributions to impulsive buying literature and practical implications for marketers in developing effective digital marketing strategies on TikTok Shop.